Half‐sandwich Iridium(III) Benzimidazole‐Appended Imidazolium‐Based N‐heterocyclic Carbene Complexes and Antitumor Application. Issue 23 (31st October 2018) - Han, Yali; Liu, Xicheng; Tian, Zhenzhen; Ge, Xingxing; Li, Juanjuan; Gao, Min; Li, Yanru; Liu, Yi; Liu, Zhe
Abstract: A series of half‐sandwich iridium(III) benzimidazole‐appended imidazolium‐based N ‐heterocyclic carbene (NHC) antitumor complexes [(η 5 ‐Cp x )Ir(C^N)Cl]Cl, where Cp x is pentamethylcyclopentadienyl (Cp*) or its biphenyl derivative (Cp xbiph ) and C^N is a NHC chelating ligand, were successfully synthesized and characterized. The Ir III complexes showed potential antitumor activity against A549 cells, at most three times more potent than cis ‐platin under the same conditions. Complexes could bind to BSA by a static quenching mode, catalyzing the change of NADH to NAD + and inducing the production of reactive oxygen species (maximum turnover number, 9.8), which play an important role in regulating cell apoptosis. Confocal microscopy showed that the complexes could specifically target lysosomes in cells with a Pearson's co‐localization coefficient 0.76 and 0.72 after 1 h and 6 h, respectively, followed an energy‐dependent cellular uptake mechanism and damaged the integrity of lysosomes. At the same time, complexes caused a marked loss of mitochondrial membrane potential. Abstract : The meat in the sandwich : Half‐sandwich Ir III NHC antitumor complexes of the type [(η 5 ‐Cpx)Ir(C^N)Cl]Cl were synthesized and characterized. The complexes enter cells by an energy‐dependent mechanism, and mainly targeted lysosomes and damaged the integrity of lysosomes. Meanwhile, the complexes could catalyze the conversion of NADH to NAD + and induce ROS, causing mitochondrial membrane dysfunction.